1991
DOI: 10.4319/lo.1991.36.6.1208
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between bacterioplankton production and limnological variables: Necessity of bacterial size considerations

Abstract: With data from eight Canadian and eight Danish lakes, we used bacterioplankton production ([3H]thymidine incorporation) in multiple regression analyses to determine to which variable it is best related. We studied two size classes: < 1 µm and 1–3 µm. For the large bacteria (1–3 µm), primary production was the only statistically significant variable. For the small bacteria (<1 µm) abundance came first, followed by chlorophyll. Small bacteria have a more uniform reproductive rate. It is suggested that phytoplank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Further, there was no significant correlation between bacterial volume and bacterial numbers in Humboldt Lake or at either depth in Redberry Lake. Our data are in agreement with those recently collected from a series of Canadian and Danish lakes which showed no clear trend towards either larger or smaller cell volumes across trophic gradients [12]. Water temperature was not a dominant factor correlated with bacterial cell volume in either Redberry or Humboldt lakes (Tables 2-4).…”
Section: Discussionsupporting
confidence: 81%
“…Further, there was no significant correlation between bacterial volume and bacterial numbers in Humboldt Lake or at either depth in Redberry Lake. Our data are in agreement with those recently collected from a series of Canadian and Danish lakes which showed no clear trend towards either larger or smaller cell volumes across trophic gradients [12]. Water temperature was not a dominant factor correlated with bacterial cell volume in either Redberry or Humboldt lakes (Tables 2-4).…”
Section: Discussionsupporting
confidence: 81%
“…Some investigators mentioned a correlation between bacterioplankton production or activity and temperature (Hagstrom & Larsson 1984, Edwars & Meyer 1986, Scavia & Laird 1987 but others found no correspondence (Findlay et al 1986, Letarte & PinelAllouI1991). Letarte & Pinel-Alloul (1991) suggest that the lack of correlation may be of 2 kinds: either other variables are too important to let temperature show its influence or the correlation is indirect. Lowest values of bacterial biomass were observed in winter, when seawater temperature, but also primary productivity, was low (low input of autochthonous labile organic material).…”
Section: )mentioning
confidence: 99%
“…Using the thymidine incorporation data (Table 1) an almost eight-fold increase in turnover times with decreasing cell size was found. This might also be the reason for the differences between the results of Simon [33,34] and Letarte and Pinel-Alloul [23,24,25] in aquatic environments, where the first author found higher turnover rates for cells smaller than 1.0 Ixm compared to larger ones, while the latter authors found the opposite result. This might also be the reason for the differences between the results of Simon [33,34] and Letarte and Pinel-Alloul [23,24,25] in aquatic environments, where the first author found higher turnover rates for cells smaller than 1.0 Ixm compared to larger ones, while the latter authors found the opposite result.…”
Section: Discussionmentioning
confidence: 92%
“…The slightly different results with regards to cell size with the two techniques were due mainly to differences in mean volume and C content of the bacteria in the different filtrates, while the DNA content per cell was assumed to be constant. Simon [33,34] used amino acid incorporation as the base for turnover calculations, while Letarte and Pinel-Alloul [23,24,25] used thymidine incorporation with a constant conversion factor to calculate turnover times. Simon [33,34] used amino acid incorporation as the base for turnover calculations, while Letarte and Pinel-Alloul [23,24,25] used thymidine incorporation with a constant conversion factor to calculate turnover times.…”
Section: Discussionmentioning
confidence: 99%